Franklin Street, ca. 1865 - Unknown (Tufts Archival Research Center, 2005)
Elevated view of houses lining Franklin Street near Devonshire Street. A pile of debris is visible in the lower-right corner of the photograph. 7 1/2 x 6 1/2, 9 3/8 x 7 1/2 overall Photographs